JURIDIC REVIEW OF GRANTING RIGHTS TO FLAT UNITS TO FOREIGN CITIZENS BASED ON THE PROVISIONS OF LEGISLATION IN INDONESIA - Karin Erliza Butar-Butar; Bambang Eko Turisno (Awang Long Law Review, 2022)
One of the efforts made by the state to improve the national economy is by increasing the number of investors working in the territory of Indonesia, then the impact of these activities causes the government to make a regulation that aims to attract foreign investors into Indonesia. Housing is a basic human need guaranteed by the constitution, because one form of arrangement made by the government is to give ownership rights to flat units to foreign citizens. The normative juridical research method uses an approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations. This approach is also known as the library approach, namely by studying various books, laws and regulations and other documents related to this research. Based on the results of research conducted, the granting of apartment unit rights to foreign nationals caused a debate, this is because the phrase property rights referred to in the basic agrarian law is known to only be attached to land that can be owned by Indonesian citizens, when reviewing the provisions of human rights law. Human rights guaranteed in the constitution give everyone the right to be able to control a right, including property rights which are the right to control objects.